Interaction of Components in the Lu-Ag-Si System at 500 ºC - Belan, B.; Dzevenko, M.; Daszkiewicz, M.; Gladyshevskii , R. (Physics and Chemistry of Solid State, 2021)
Isothermal section of the Lu-Ag-Si system at 500ºC was studied by means of X-ray powder diffraction, microstructure and EDX-analyses in the whole concentration range. The existence of earlier reported binary compounds LuAg4, LuAg2, LuAg and LuSi2, LuSi, Lu5Si3, Lu5Si4 was confirmed. New binary compound Lu3Si5 (own str. type) was found. Almost none of the binary silicides dissolve more than 5 at.% of third component. The exception is the existence of the substitution type solid solutions based on LuAg2 (MoSi2-type structure), which dissolves up to 20 at.% Si, as well as on Lu5Si3 (Mn5Si3-type structure), which dissolves up to 15 at.% Ag. The crystal structure of the LuSi compound was redetermined by X-ray single crystal diffraction (TlI-type, space group Cmcm, a = 4.1493(3), b = 10.2641(7), c = 3.7518(2) Å, R = 0.0173, wR = 0.0415 for 173 independent reflections). No ternary compound is observed in the Lu-Ag-Si system.